Problemy analizy proelastycznego doskonalenia systemu informacyjnego - Skwarnik, Marek (Problems of Pro-Elastic Information System Improvement Analysis, 2007)
The pro-elastic approach to the improvement of management information systems requires an extensive and comprehensive analysis of elements and processes. In this paper the author proposes the new model of information system elasticity, considering the problem from both static and dynamic perspective.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (10); 2007; nr 1150, s. 187-196